Evaluación delas variables e desempeño cooperativo con un enfoque en el buen vivir en la provincia de Pichincha. - Faubla Salazar, Gema Johanna (2017)
In order to evaluate the cooperative performance of savings and credit with a focus on Good Living in the province of Pichincha, three methodological phases were carried out, where the variables of cooperative performance were identified in the first instance through the bibliographical search of Principles of the Popular and Solidarity Economy, Good Living, Cooperativism and Corporate Social Responsibility, and then with the help of qualified experts in each of the cooperatives, select the indicators of the variables to be studied through the application of the Torgerson Mathematical Model and in this way to allow the implementation of the evaluation tool, which was applied to managers, employees and partners of the 7 cooperatives which were willing to collaborate in the process and based on the results obtained, it was possible to know the poor performance in certain indicators of each principle, which made it possible to draw up an improvement plan to potentiate the variables of the cooperative performance of savings and credit, through the proposal of improvement actions for those indicators that, with the use of the Pareto Diagram, resulted in early intervention needs, thus promoting the achievement of Good Living in the cooperatives investigated.